No color is my kind : Eldrewey Stearns and the desegregation of Houston - Cole, Thomas R., 1949- (University of Texas Press, 2021)
"In 1984, Thomas Cole met Eldrewey Stearns in a Galveston psychiatric hospital. Stearns, a fifty-two-year-old Black man, complained that although he felt very important, no one understood him. Over the course of the next decade, Cole and Stearns, in a tumultuous and often painful collaboration, recovered Stearns's life before his slide into mental illness-as a young boy in Galveston and San Augustine and as a civil rights leader and lawyer who sparked Houston's desegregation movement between 1959 and 1963"--